Clinical Relationship between Steatocholecystitis and Gallbladder Contractility Measured by Cholescintigraphy - Chang Seok Bang; Yong Sub Lee; Jai Hoon Yoon; Youn Jeong Kim; Jin Bong Kim; Dong Joon Kim (Gastroenterology Research and Practice)
Objective. Contractility of gallbladder is known to be decreased in fatty gallbladder diseases. However, clinical estimation data about this relationship is still lacking. The aim of this study was to investigate the association between steatocholecystitis and contractility of gallbladder. Methods. Patients with cholecystitis (steatocholecystitis versus nonsteatocholecystitis) who underwent cholescintigraphy before cholecystectomy were retrospectively evaluated in a single teaching hospital of Korea. The association of steatocholecystitis with contractility of gallbladder, measured by preoperative cholescintigraphy, was assessed by univariable and multivariable analysis. Results. A total of 432 patients were finally enrolled (steatocholecystitis versus nonsteatocholecystitis; 75 versus 357, calculous versus acalculous cholecystitis; 316 versus 116). In the multivariable analysis, age (OR: 0.94, 95% CI: 0.90–0.99, P=0.01) and total serum cholesterol (OR: 1.02, 95% CI: 1.01–1.04, P=0.04) were related to steatocholecystitis in patients with acalculous cholecystitis. Only age (OR: 0.97, 95% CI: 0.94–0.99, P=0.004) was significantly related to steatocholecystitis in patients with calculous cholecystitis. However, ejection fraction of gallbladder reflecting contractility measured by cholescintigraphy was not related to steatocholecystitis irrespective of presence of gallbladder stone in patients with cholecystitis. Conclusion. Ejection fraction of gallbladder measured by cholescintigraphy cannot be used for the detection or confirmation of steatocholecystitis.